Comparison of linezolid and daptomycin for the treatment of vancomycin-resistant enterococcal bacteremia. (February 2019) - Narayanan, Navaneeth; Rai, Rena; Vaidya, Parth; Desai, Avani; Bhowmick, Tanaya; Weinstein, Melvin P.
Vancomycin-resistant enterococcal bacteremia (VRE-B) is a common nosocomial infection associated with significant morbidity and mortality. Daptomycin and linezolid are primary treatment options although definitive clinical data to assess comparative therapeutic effectiveness are lacking. This study assessed the outcomes of patients with VRE-B treated with linezolid or daptomycin. This was a single-center, retrospective cohort study evaluating adult patients with VRE-B treated with either daptomycin or linezolid admitted between January 2012 and August 2016 at a tertiary care, academic medical center. The primary outcome was clinical failure, a composite outcome defined as 14-day in-hospital mortality, microbiologic failure, or relapse of VRE-B. Secondary outcomes included 14-day in-hospital mortality, microbiologic failure, relapse of VRE-B, duration of VRE-B, and antibiotic failure. A multivariate logistic regression model was performed to adjust for potential confounding variables. A total of 93 patients were included ( n = 62 for linezolid and n = 31 for daptomycin). All blood isolates were Enterococcus faecium . Overall clinical failure was 55.9% and 14-day in-hospital mortality was 21.5%. There was a significantly higher rate of clinical failure in the daptomycin group as compared with the linezolid-treated patients (74.2% versus 46.8%; p = 0.01; respectively). In multivariate logistic regression analysis, there was a significantly higher odds of clinical failure for patients treated with daptomycin as compared with linezolid (adjusted odds ratio 2.89; 95% confidence interval 1.08–7.75) after adjusting for confounders. Secondary outcomes were not statistically significantly different between study groups. Standard-dose (6 mg/kg) daptomycin treatment was associated with a higher rate of clinical failure as compared with linezolid treatment.